Der Bauernkrieg. Ein Systemkonflikt an der Wende vom Mittelalter zur Neuzeit - Florian Ambach (Historia.scribere)
The following paper aims to examine if and how the Peasants’ War was connected with the Protestant Reformation. In order to answer this question, various models of society developed by the peasants will be analysed. The specific characteristics of the different, loosely connected rebellions, which were summarised and idealised to a united movement, the so-called Peasants’ War, by later historiography, will be pointed out through the example of four different rebellious areas.